Pension Reforms in Mauritius : Fair and Fast-Balancing Social Protection and Fiscal Sustainability - Soto, Mauricio (IMF Working Papers; Working Paper ;, 2015)
Despite important past reforms, the ageing population of Mauritius threatens the sustainability of its pension system. This paper examines how pension spending might increase without reforms and discusses reforms options. The findings suggest that unifying the retirement age and indexing it to life expectancy would contribute most significantly to secure and sustainable pensions. The poverty reducing objective of the universal pension can be improved by better targeting. The old age protection objective of the National Pension Fund could be strengthened by increasing contribution and replacement rates. Implementing changes faster should result in less drastic future changes and fairer outcomes.